Anguish (s) and dialogues between Graciliano Ramos and popular knowledge. - da silva, adenilton moises; da Silva, Everaldo Fernandes (Universidade Estadual de Campinas, 2021)
This article reflects the phenomenon of anguish as a constituent of the human condition, which materializes in different modes and expressions, corresponding to the time and space in which human subjects are historically and geographically located. As it is not a strictly philosophical or psychoanalytical approach, we chose to establish a cut through the construction of a dialogue about the Anguish described by the northeastern novelist Graciliano Ramos and the distressing feelings of illiterate popular subjects, thus elaborating an interlocution with the life and learning of excluded subjects who, in the midst of small, almost daily hardships and utopias, produce meanings, knowledge and new resilience agendas in order to be / be in life.